Plasma C-Reactive Protein and Pentraxin-3 Reference Intervals During Normal Pregnancy - Wirestam, Lina; Pihl, Sofia; Saleh, Muna; Wetterö, Jonas; Sjöwall, Christopher (Frontiers in Immunology, 2021)
Although several biomarkers are available to monitor the acute phase response, the short pentraxin C-reactive protein (CRP) is dominating in clinical practice. The long pentraxin 3 (PTX3) is structurally and functionally related to CRP, but not liver-derived. In addition, increased levels of PTX3 have been linked to preeclampsia. Reference intervals are usually based on healthy blood donors. Several physiological and immunological alterations occur during normal pregnancy with subsequent potential effects on blood analytes. Hence, this study aims to determine pregnancy-specific reference intervals for CRP and PTX3. Longitudinal clinical data and blood plasma samples from the 1st, 2nd and 3rd trimester of 100 healthy, non-medicating, females aged 18–40 at the time-point of conception were available to us. High‐sensitivity CRP measurements were performed by turbidimetry and enzyme-linked immunosorbent assay (ELISA) was used to quantify PTX3. CRP and PTX3 levels followed each other during the first two trimesters and both increased during the third trimester. CRP showed a median of 4.12 mg/L in the third trimester, and were significantly higher compared to the first (median 2.39 mg/L, p<0.0001) and the second (median 2.44 mg/L, p=0.0006) trimesters. In the third trimester PTX3 levels reached a median of 7.70 µg/L, and were significantly higher compared to the first (median 3.33 µg/L, p<0.0001) and the second (median 3.70 µg/L, p<0.0001) trimesters. Plasma albumin was inversely correlated with CRP (rho=0.27, p<0.0001), but not with PTX3. In conclusion, it is important to consider pregnancy-specific reference values as elevations of CRP and PTX3 during the later phase may occur in absence of infection.